The Influence of Product Quality, Service Quality, and Promotions on Clothing Purchase Decisions at GAIA Sho - Anjani, Devi; Alim, Muchammad Rully Sjahirul (Economics and Business International Conference Proceeding, 2024)
This research is entitled The Influence of Product Quality, Service Quality, and Promotion on Clothing Purchase Decisions at the Gaia Shop. This research aims to determine the influence of product quality, service quality and promotion on clothing purchasing decisions at the Gaia Shop. This research used the Slovin formula to obtain a sample of 93 respondents. The sampling technique used in this research is a nonprobability sampling technique with the type of Accidental Sampling. The data analysis method in this research is quantitative analysis.Hypothesis testing uses the t test, F test, and Determination test. Apart from that, the data normality test, multicollinearity test and heteroscedasticity test were also used. Product quality has a positive and significant effect on purchasing decisions, service quality has a negative and insignificant effect on purchasing decisions, promotion has a positive and significant effect on purchasing decisions.